Exploration of High elevation liana colonies on Mt. Slamet, Central Java, Indonesia - WS Hoover; Deden Girmansyah; Harry Wiriadinata; James M. Hunter (BRIN Publishing (Penerbit BRIN), 2009)
One hundred forty-five individual lianas were distributed on 2 East facing ridges on the second highest mountain on Java, Mt. Slamet (3418 m.), Central Java, Indonesia. Twenty one colonies were observed on small flat areas on ridges. The liana species observed include: Embelia pergamacea, Toddalia asiatica, Elaeagnus latifolia, Schefflera lucida, Vaccinium laurifolium and Lonicera javanica. Diameter of each liana was measured and liana density/flat area calculated. Floristic collecting was under- taken within the elevational gradient of liana distribution. Data suggest an ecotone transition from lower to upper mon- tane forest is observed between 2200 and 2300 m, though forest types are difficult to determine due to disturbance caused by fire at the upper elevations. Observing lianas at these unusuall high elevations with near pluvial rainfall, con- tradict established scientific theory concerning global distribution and abundance of lianas.